Multi-step adhesive cementation versus one-step adhesive cementation: Push-out bond strength between fiber post and root dentin before and after mechanical cycling - Amaral, Marina [UNESP]; Rippe, Marilia Pivetta [UNESP]; Bergoli, Cesar Dalmolin [UNESP]; Monaco, Carlo; Valandro, Luiz Felipe (My University, 2011)
This study evaluated the effects of mechanical cycling on resin push-out bond strength to root dentin, using two strategies for fiber post cementation. Forty bovine roots were embedded in acrylic resin after root canal preparation using a custom drill of the fiber post system. The fiber posts were cemented into root canals using two different strategies (N = 20): a conventional adhesive approach using a three-step etch-and-rinse adhesive system combined with a conventional resin cement (ScotchBond Multi Purpose Plus + RelyX ARC), or a simplified adhesive approach using a self-adhesive resin cement (RelyX U100). The core was built up with composite resin and half of the specimens from each cementation strategy were submitted to mechanical cycling (45 degree angle; 37°C; 88 N; 4 Hz; 700,000 cycles). Each specimen was cross-sectioned and the disk specimens were pushed-out. The means from every group (n = 10) were statistically analyzed using a two-way ANOVA and a Tukey test (P = 0.05). The cementation strategy affected the push-out results (P < 0.001), while mechanical cycling did not (P = 0.3716). The simplified approach (a self-adhesive resin cement) had better bond performance despite the conditioning. The self-adhesive resin cement appears to be a good option for post cementation. Further trials are needed to confirm these results.